FAKTOR DETERMINAN BALITA STUNTING PADA DESA LOKUS DAN NON LOKUS DI 13 KABUPATEN LOKUS STUNTING DI INDONESIA TAHUN 2019 - Yurista Permanasari; Ika Saptarini; Nurilah Amalia; aditianti aditianti; Amalia Safitri; Nuzuliyati Nurhidayati; Yunita Diana Sari; Prisca Pretty Arfines; Irlina R. Irawan; Dyah Santi Puspitasari; Febriani Syahrul; Budi Setyawati; Rika Rachmawati; Elisa Diana Julianti; Rika Rachmalina; Andi Susilawati; Novianti Sihombing; Sisca Dwi Kumlasari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2021)
ABSTRACT The implementation of government policies in stunting prevention has been carried out from the central level to the village level. The Ministry of Home Affairs annually establishes stunting locus villages in 34 provinces. At the stunting locus village, sensitive and specific interventions were carried out. Many factors influence the prevalence of stunting. This study aims to determine the determinants of stunting in locus and non-locus villages in 13 stunting locus districts in Indonesia. This study was a quantitative study with a cross-sectional design. The study was conducted in 13 districts of stunting locus. Each district was chosen one sub-district which was then selected one locus of stunting village and one village of non locus. In each village 90 children were selected. Data analysis was carried out univariate, bivariate, and multivariate with logistic regression test to see the relationship between independent and dependent variables after being controlled by several variables. The results showed that 20 percent lower chance of stunting in locus villages than non locus villages. Toddlers who are breastfed for more than 24 months have a 1.7 times risk of becoming stunted. Toddlers who do not do early initiation of breastfeeding have a 1.5 times risk of becoming stunted compared to toddlers who do early initiation of breastfeeding. High maternal education can prevent stunting 2 times compared to mothers with low education. The selection of stunting locus villages affects the prevalence of stunting. In addition, several determinant factors influence the incidence of stunting, namely the sex of the child, the duration of breastfeeding more than 24 months, the child's age, early initiation of breastfeeding, growth monitoring, the mother's age and the mother's education. ABSTRAK Implementasi kebijakan pemerintah dalam pencegahan stunting telah dilaksanakan mulai dari tingkat pusat sampai tingkat desa. Kementerian Dalam Negeri setiap tahun menetapkan desa lokus stunting di 34 provinsi. Pada desa lokus stunting dilakukan intervensi sensitif dan spesifik. Banyak faktor yang mempengaruhi prevalensi stunting. Studi ini bertujuan untuk mengetahui faktor determinan kejadian stunting pada desa lokus dan non lokus di 13 kabupaten lokus stunting di Indonesia. Studi ini merupakan studi kuantitatif dengan desain potong lintang. Penelitian dilakukan di 13 Kabupaten lokus stunting, setiap kabupaten dipilih satu kecamatan yang kemudian dipilih satu desa lokus stunting dan satu desa non lokus. Pada setiap desa dipilih 90 balita. Analisis data dilakukan secara univariat, bivariat, dan multivariat dengan uji regresi logistik untuk melihat hubungan variabel bebas dan terikat setelah dikontrol oleh beberapa variabel. Hasil penelitian memperlihatkan bahwa peluang terjadinya stunting 20 persen lebih rendah di desa lokus dibanding desa non lokus. Balita yang mendapatkan ASI lebih dari 24 bulan berisiko 1,7 kali menjadi stunting. Balita yang tidak melakukan inisiasi menyusui dini (IMD) berisiko 1,5 kali menjadi stunting dibandingkan dengan balita yang melakukan IMD. Pendidikan ibu yang tinggi dapat mencegah kejadian stunting 2 kali dibandingkan ibu berpendidikan rendah. Pemilihan desa lokus stunting memengaruhi kejadian stunting. Selain itu, terdapat beberapa faktor determinan yang memengaruhi kejadian stunting yaitu jenis kelamin anak, durasi menyusui ASi lebih dari 24 bulan, usia anak, IMD, pemantauan pertumbuhuan, umur ibu dan pendidikan ibu. [Penel Gizi Makan 2021, 44(2):79-92]